Characterization of Special Grain Boundaries and Triple Junctions in CuxNi1‐x Alloys upon Deformation and Annealing. Issue 4 (18th January 2019) - Emeis, Friederike; Leuthold, Jörn; Spangenberg, Katharina; Peterlechner, Martin; Wilde, Gerhard
Abstract : We compare two quantities to describe a microstructure: the length fraction of Σ 3/ Σ 9‐grain boundaries and the number fraction of Σ 3‐x‐x/ Σ 3‐ Σ 3‐ Σ 9‐triple junctions using Cu, Ni and four of their alloys in several microstructural states. The fractions of Σ 3‐grain boundaries show similar tendencies as the respective fractions of Σ 3‐x‐x‐triple junctions in relation to the grain size upon deformation and annealing. However, the fraction of Σ 9‐grain boundaries stagnates at certain grain sizes, while there is still a considerable change of Σ 3‐ Σ 3‐ Σ 9‐triple junctions during grain growth, meaning that the Σ 3‐ Σ 3‐ Σ 9‐triple junction microstructure is still evolving. To analyze the evolution of the triple junction microstructure, a program, such as pythorient, is necessary. Abstract : Descriptions of microstructures: python‐script (freely available) to easily evaluate special‐triple junctions from EBSD‐measurements, enabling the evaluation of large data sets. Comparison between fractions of special‐grain boundaries and special‐triple junctions in relation to the grain size of different microstructural states in Cu x Ni x ‐1, obtained by deformation/annealing: Maximum obtainable fractions of Σ 3‐grain boundaries and of Σ 3‐ x ‐ x ‐triple junctions are similar for all compositions. Even though the length fraction of Σ 9‐grain boundaries stagnated, the number fraction of Σ 3‐ Σ 3‐ Σ 9‐triple junctions still increased during grain growth.